Accessory and Incomplete Lung Fissures: Clinical and Histopathologic Implications. Issue 4 (July 2021) - Bayter, Paula A.; Lee, Gregory M.; Grage, Rolf A.; Walker, Christopher M.; Suster, David I.; Greene, Reginald E.; Gilman, Matthew D.; Lanuti, Michael; Stowell, Justin T.
Abstract : Objective: This article reviews the anatomy, histology, and disease processes of pulmonary fissures, with emphasis on clinical implications of accessory and incomplete fissures. Conclusion: Accessory and incomplete pulmonary fissures are often overlooked during routine imaging but can have profound clinical importance. Knowledge of fissure anatomy could improve diagnostic accuracy and inform prognosis for oncologists, interventional pulmonologists, and thoracic surgeons. Abstract : Supplemental Digital Content is available in the text.